2012
DOI: 10.22146/gamaijb.5437
|View full text |Cite
|
Sign up to set email alerts
|

Is Earnings Management Informational or Opportunistic? Evidence from ASEAN Countries

Abstract: This study explores the informational and opportunistic characteristics of earnings management in ASEAN countries. Earnings management has an impact on the profitability of the companies. A positive relation between earnings management and future profitability reveals that earnings management is informational. However, negative a relation between earnings management and future profitability indicates that earnings management is opportunistic.This study uses data from the OSIRIS database. Four hundred and eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Characteristics of earnings management in south-east Asia countries (Indonesia, Philippine, Singapore, Thailand, and Malaysia) is not similar (Wardani & Kusuma, 2012). By focusing on accruals based earnings management and real earnings management, the researchers found out that real earnings management is less aggressive in Indonesia and Philippine compared to the others countries.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…Characteristics of earnings management in south-east Asia countries (Indonesia, Philippine, Singapore, Thailand, and Malaysia) is not similar (Wardani & Kusuma, 2012). By focusing on accruals based earnings management and real earnings management, the researchers found out that real earnings management is less aggressive in Indonesia and Philippine compared to the others countries.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…Moreover, the literature demonstrated evidence that AEM has a significant association with REM, both as the substitution and complementary methods, in different country, such as China, Japan, Taiwan, India, Germany, Canada, and America (Achleitner et al, 2014;Chen et al, 2012;Das et al, 2017;Lee & Swenson, 2011;Matsuura, 2008;Zhu et al, 2015). The study in Thailand by Wardani and Kusuma (2012) examined the influence of earnings management on future performance using 116 Thai firms listed in the period 2004-2009, and the result found that AEM is not affected by future performance; in contrast, managers use REM as a business strategy to achieve a better performance. However, there is still aa lack of the evidence that clearly reflects the relationship between AEM and REM in Thailand.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…To study earnings management in Thailand, Wardani and Kusuma (2012) researched Thai firms listed during [2004][2005][2006][2007][2008][2009], and they found that AEM is not affected by future performance; in contrast, REM includes sale acceleration, overproduction, and discretionary expenses, as described by Roychowdhury (2006) and is used as a business strategy to achieve better performance. While a prior study found the effects of earnings management on the quality of financial reports, Intakhan and Ussahawanitchakit (2009) collected data from the Stock Exchange of Thailand (SET) by dividing earnings management into four categories, namely, unreasonable change in accounting policy, wealth transfer misrepresentation, information distortion, and corporate-based concern of accounting choice.…”
Section: Introductionmentioning
confidence: 99%
“…The independent variables in this research are Deferred Tax Expense, Current Tax Expense, and Asset Growth. The earnings management variable uses discretionary accrual (DAC) proxy, which is the calculation of the modified Jones model in 1991 (Wardani & Kusuma, 2012).…”
Section: Methodsmentioning
confidence: 99%